Inventory of lice of mammals and farmyard chicken in North-eastern Algeria - Mohamed Nadir Meguini; Souad Righi; Fayçal Zeroual; Khelaf Saidani; Ahmed Benakhla (Veterinary World, 2018)
Background and Aim: Lice are permanent ectoparasites, extremely specific to their hosts. Their great importance in veterinary medicine remain significant, they can cause their direct pathogenic actions like irritability, dermatitis, anemia, decreased weight gain, and milk production. The purpose of this work was to made the first time an inventory of mammalian lice in North-eastern Algeria. Materials and Methods: Our survey of lice infestation was conducted on several animal species from five provinces of North-eastern Algeria. A total of 57 cattle, 83 sheep, 77 goats, 111 wild boars, and 63 farmyard chickens were examined. The collection of lice was carried out much more in mammals and chickens during the winter period. Lice were collected either manually or using brushing and kept in flasks containing 70% ethanol. The identification of lice was achieved in the laboratory using a binocular loupe. Results: Concerning cattle, 63% and 27% of those examined subjects from Souk-Ahras and Guelma study areas, respectively, were carriers of lice. Damalinia bovis was the louse most frequently found on cattle in these two regions. Three other species were identified in Souk-Ahras: Haematopinus eurysternus (25%), Linognathus vituli (10%), and Solenopotes capillatus (5%). Regarding sheep, 39% and 24% of examined animals in Souk-Ahras and Guelma, were carrying lice. Damalinia ovis was the most frequently encountered lice on sheep in both regions. Linognathus ovillus also was identified in Souk-Ahras, representing 0.3% of the collected lice. Concerning goats, 53% and 30% of examined animals in Souk-Ahras and Guelma, were parasitized of lice. Two species of lice were found: Damalinia caprae and Linognathus africanus. For farmyard chickens, 69% and 100% of the farmyard chicken in Souk-Ahras and Mila were parasitized by lice, respectively. Menopon gallinae was the most frequently encountered louse in farmyard chicken in both regions. Eight other species were identified in Mila and four other species only in Souk-Ahras. Finally, 25% and 28% of the wild boars in Annaba and El Tarf were parasitized by lice, respectively. Haematopinus suis was the only species found on wild boars in both regions. Conclusion: These results are to be taken into account for lice control schemes and louse-borne diseases.